A new Schistura from the Salween basin in western Yunnan (Teleostei: Nemacheilidae) - Endruweit, Marco (Zootaxa, 2017)
River loaches of the genus Schistura McClelland 1838 are small, elongated, benthic fishes of the family Nemacheilidae. Species in the genus are part of a subsistence fishery in several Southeast Asian countries due to their tasty flesh and relative abundance in suitable habitats. Fluvial environments with gravelly bottoms in tropical and subtropical regions can be co-inhabited by several species of nemacheilid loaches. Kottelat (1990) reported up to six different species coexisting in Indochinese streams in some instances. With about 200 valid taxa, Schistura is the most diverse genus within the family Nemacheilidae (Kottelat 2012). Species allocated within this genus share a moderately arched mouth, a medially notched lower lip, lack lateral labial pads, possess an air bladder without a secondary chamber, and reach a maximum standard length between 19 and 120 mm (Kottelat 1990; Ou et al. 2011).